2022
DOI: 10.1182/hematology.2022000409
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and screening for neurocognitive impacts of therapy

Abstract: Long-term survivors of pediatric hematologic malignancies are at elevated risk for neurocognitive impairment. Such impairment manifests in different ways at different times during survivorship, with deficits in processing speed, attention, and memory often appearing before deficits in executive function, intelligence, and academics. Survivors exposed to therapies that directly target the central nervous system (CNS), as is the case in acute lymphoblastic leukemia, may demonstrate subtle deficits during frontli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“… 6 , 16 The cohort of pediatric cancer survivors followed up at SJCRH constitutes a unique dataset. Survivors of treatment for childhood cancer are already known to have poorer neurocognitive performance than their unaffected peers, 18 and a recent study showed that experiencing bacteremic sepsis during leukemia treatment was associated with declining attention performance over time. 16 Here, we show that the increase in attention impairment and higher-grade neurocognitive dysfunction do not appear driven by higher proportions of neurological conditions such as cerebrovascular accidents or seizures among those with sepsis.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 16 The cohort of pediatric cancer survivors followed up at SJCRH constitutes a unique dataset. Survivors of treatment for childhood cancer are already known to have poorer neurocognitive performance than their unaffected peers, 18 and a recent study showed that experiencing bacteremic sepsis during leukemia treatment was associated with declining attention performance over time. 16 Here, we show that the increase in attention impairment and higher-grade neurocognitive dysfunction do not appear driven by higher proportions of neurological conditions such as cerebrovascular accidents or seizures among those with sepsis.…”
Section: Discussionmentioning
confidence: 99%